Aplikasi Smartphone GIS (Geografik Information System) Pencarian Sekolah SMK Daerah Cirebon Berbasis Android - Sari Noorlima Yanti; Endah Budiyati; Esti Setiyaningsih (Program Studi Teknik Informatika Universitas Pamulang, 2020)
GIS application is an Android-based application that contains information about the user's location and user address located. The problem of finding information about the existence of a school location with the help of maps on internet facilities. The method of finding information with the GIS contained in this application includes a map as well as the location of Vocational High Schools in the Cirebon Region. Other information includes the address, telephone number and directions from the user's location to the destination school. This application is created using the Action Script programming language and the software uses Eclipse. Android is an operating system platform that is open or opensource. Android-based java programming language code that is multiplatform. Java-based application developers can freely build applications openly that can run on many Android-based devices. The results of this study are to provide information to Android device users about the location of Vocational Schools in the Cirebon Region.